Surgery in older patients: learning from shared decision-making in intensive care. (November 2022) - Fowler, Alexander J.; Stephens, Timothy J.; Partridge, Judith; Dhesi, Jugdeep
Summary: An increasing number of older patients are having surgical treatments. Similar to older patients admitted to intensive care, they present with additional problems including multimorbidity, frailty, and cognitive impairment. In both intensive care and surgical settings, comprehensive assessment can inform targeted interventions and shared decision-making. We explore the challenges faced by older patients, and by the clinicians treating them.